(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
2019 will be significant for the Russian party system. First, near 30 years ago, Article 6 of the USSR Constitution was abolished, formally creating the basis for a modern Russian multi-party system. Secondly, next year ends the 7-year period for new political parties, formed on the basis of changes in the Law on Political Parties of 2012 to become active political actors. All parties that do not conduct political activities and have not even formally participated in the elections will be eliminated. In this connection, there is a need to evaluate the past period, to answer the interrelated questions: in what state is the Russian party system? What is its configuration? Will it affect the elimination of some of the parties? The answers to them will be part of a broader, more permanent discussion about the role and place of parties in the Russian political system. The state of the Russian parties will be analyzed in the context of world trends of "party change", the transformation of forms, functions and methods of activity of political parties, their models in the semantic space of Russian politics, and the arrangement of party political forces. Particular attention will be paid to the personnel potential and peculiarities of functioning of the Russian parties at the regional level, because it serves as a criterion for assessing the activities of parties and the formation of electoral preferences for the majority of citizens. In addition, internal processes taking place in Russian parties, especially those formed after 2012 are most noticeable in the regions. In aggregate, the data presented will make it possible to identify trends in the development of the party system of the Russian Federation in the short term.